PENGARUH KEPUASAN, KEPERCAYAAN DAN KEMUDAHAN PENGGUNAAN TERHADAP LOYALITAS PELANGGAN PADA MARKETPLACE SHOPEE DI KECAMATAN MEDAN HELVETIA - Alfriado Leonard Noprian Dolok Saribu; Dimas; Hesti Sabrina; Hery Syahrial; Haryaji Catur Putera Husman (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Technology is developing very rapidly and continues to change from year to year. Therefore, the latest digital marketing trends will continue to emerge which are adapted to the conditions and situations of that year, but there are still some groups of people who do not understand the importance of digital trends, because competition for marketplaces or online shopping sites in Indonesia is currently getting tighter, the competition that is happening is not only from domestic shopping sites but also foreign ones that have entered the domestic market. This research aims to analyze the influence of satisfaction, trust and ease of use on customer loyalty in the Shopee marketplace in Dwikora sub-district, Medan Helvetia sub-district. This type of quantitative research with the independent variables used in this research is satisfaction, trust and ease of use and the dependent variable used is customer loyalty. The population used in this research is all people in Medan Helvetia sub-district. This research took samples using a purposive sampling method and there were 100 respondents who were deemed worthy of being research criteria. The research results show that partially and simultaneously satisfaction, trust and ease of use have a significant positive effect on customer loyalty.